A Simple g-C3N4/TNTs Heterojunction for Improving the Photoelectrocatalytic Degradation of Methyl Orange. Issue 11 (29th November 2021) - Zeng, Linsheng; He, Zichun; Luo, Yongping; Xu, Jitao; Chen, Jiansheng; Wu, Li; Huang, Ping; Xu, Shunjian
Abstract : In this work, highly ordered titanium dioxide nanotube arrays (TNTs) were first prepared by anodic oxidation method. Then, g-C3 N4 /TNTs heterojunctions were prepared by ultrasonically loading graphitic carbon nitride (g-C3 N4 ) onto the TNTs. The morphology and crystal structure of TNTs and g-C3 N4 /TNTs were characterized by SEM/TEM and XRD. The photoelectrocatalytic (PEC) degradation of methyl orange (MO) by TNTs and g-C3 N4 /TNTs was studied in a PEC degradation system. The photocatalytic (PC), electrocatalytic (EC), and PEC degradation properties were compared, and the effect of pollutant concentration on the degradation performance of the catalysts was analyzed. According to the experimental results, the degradation rate of MO with TNTs only reaches 65.1% after 120 min, while the degradation rate of MO with g-C3 N4 /TNTs reaches 84.6% in the same time. Due to the synergistic effect of light and electricity, the PEC degradation efficiency of the two catalysts is greater than the sum of PC and EC degradation, proving that g-C3 N4 /TNTs heterojunctions provide excellent PEC performance for the degradation of MO.